[Congregational and Presbyterian Churches of Washington], - Hooker, George Ellsworth, 1861-1939
In July 1892, George E. Hooker of Medical Lake, Washington sent out a form to churches in Washington asking for "the facts respecting the multiplication of churches in the small and moderate sized towns of our State, and particularly as the part which Home Missionary funds play in the matter." The form asked a number of questions, which pastors sent back and sometimes wrote letters as well. This small collection includes the responses from Skokomish, Christopher, Roy, Port Gamble, Eagle Harbor, Fidalgo, Gig Harbor, and a particularly long letter from Robert Boyd of Port Townsend. Hooker sent out this survey in 1892 and wrote an article called "The Problem of Interdenominational Comity Among Country Churches in Home Missionary Territory." He gave this paper at the International Christian Conference in Chicago in 1893. He cites the responses he received in these questionnaires.